The eHealth literacy scale (eHEALS): is it suitable for health education nursing officers in Sri Lanka? - Millawage Supun Dilara Wijesinghe; Sherine J. Balasingham; Balangoda Muhamdiramlage Indika Gunawardana; Weerasinghe Mudiyanselage Prasad Chathuranga Weerasinghe; Rajapaksha Mudiyanselage Nayani Umesha Rajapaksha; Praveen Shankar Nagendran; Dhanaja Kaushalya Illangasinghe; Eranda Janaka; Ranjith Batuwanthudawe; Palitha Karunapema (Health Literacy and Communication Open)
Effective use of electronic health tools requires a specific set of skills. These skills can be assessed using valid eHealth literacy measurement tools. This study aimed to validate the widely used eHEALS scale among Health Education Nursing officers (HENOs) working in government hospitals in Sri Lanka. We sent eHEALS questionnaires to all hospitals in the country where HENOs were present. The sample size used in the validation study was 80. Exploratory Factor Analysis (EFA) and reliability analyses were performed. The results of the EFA fit into a unidimensional model (60.97% of the variance explained). The Cronbach’s alpha for the scale was 0.90. Our study found that the original version of the eHEALS was unidimensional, as reported by the original authors. It is sufficiently valid and reliable for health education nursing officers in Sri Lanka.